Direct Lithography for Regulating Multiple Properties of Organic Semiconductors via Photo‐Crosslinkers - Yueping Lai; Liang‐Wen Feng (Macromolecular Materials and Engineering)
Abstract Photo‐crosslinkers, as materials with negative photoresist characteristics, are applied in the direct lithography process of organic semiconductor devices. Compared to commonly used organic lithography processes, the direct lithography process only requires three steps: spin‐coating, exposure, and development, to achieve optical patterning of the organic semiconductor channel, eliminating the need for complex procedures such as protection, baking, etching, and transfer. Furthermore, during this process, the photo‐crosslinker remains in the blended film, subsequently influencing the crystalline structure and morphology of the semiconductor film. These alterations will further impact multiple properties of the organic film. By utilizing this characteristic, the design of photo‐crosslinker can effectively regulate and enhance the tensile properties, charge carrier mobility, stability, and dielectric properties of the device. This approach effectively enables high‐precision patterning of organic integrated circuits while synchronously enhancing their various performance attributes. Although there are some relevant reports, a systematic summary and organization of the impact of these photo‐crosslinkers on semiconductors remains absent. For the future development of direct lithography, systematic organization is crucial. Therefore, this review systematically classifies and summarizes the functions of photo‐crosslinkers in organic thin film devices, providing guidance for the design of novel photo‐crosslinkers in direct lithography and improve multiple properties of semiconductor devices.